Analisis Kinerja Keuangan Dengan Pendekatan Altman Untuk Memprediksi Tingkat Kebangkrutan Perusahaan Yang Terdaftar Pada Saham Jakarta Islamic Index Di Bursa Efek Indonesia - Nurkhayati Nurkhayati; Erna Listianingsih; Nurmala Nurmala (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2014)
One of the technical analysis of the company's bankruptcy is using discriminant analysis developed by Altman with a model known is the Z-Score. The purpose of this paper is to investigate the possibility of bankruptcy rate in the companies which is included in the Jakarta Islamic Index (Jll) at the Indonesian Stock Exchange by the method of Altman Z-Score. Samples were taken by using purposive sampling technique with a total sample of six companies. The study found that from six companies, five companies declared bankrupt and the rest of them is to be declared bankrupt. It means that the hypothesis is accepted in where the companies which is included in the Jakarta Islamic Index experienced bankruptcy.